R. A. A. Wiranatakusumah V: Tokoh republikan sebagai Wali Negara Pasundan (1948 – 1950) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
This study aims to analyze the political role of R.A.A Wirantakusumah V in 1948-1950 which includes his work when he was Republican, became Mayor of Pasundan. The method in this research is the historical method which consists of several stages, namely: heuristics, source criticism (external and internal), interpretation and historiography. Through this research, it can be known, Revolution, there were two opposing groups. Second, role of R. A. A. Wiranatakusumah V work as the Mayor of Pasundan is very central as a liaison between the Republic of Indonesia and the Pasundan State. Although in the Pasundan State there are many factions and groups, R.A.A. Wiranatakusumah V is a Republican who holds fast to the independence and struggle of the Republic of Indonesia. And the end of R. A. A. Wiranatakusumah V political activities was marked by the end of his position as Mayor of Pasundan which was marked by the end of the Pasundan State in 1950 rejoining the of Indonesia.
Keywords: R. A. A. Wiranatakusumah V; Republikan; Federalis; Pasundan State